Growth, Development and Reproduction of Meadow Moth Loxostege sticticalis Fed on Pea Seedlings Grown Under Elevated CO2 - Jingxian Zhou; Zun Xu; Zuoheng Yu; Huirong Mai; Jiacheng Huang; Xiaoli Chang; Fajun Chen (Agronomy)
To comprehensively investigate the impacts of increased atmospheric CO2 concentrations on the growth, development and reproduction of the meadow moth Loxostege sticticalis when fed on pea plants (Pisum sativum), in this experiment, we simulated the two CO2 conditions: ambient CO2 (i.e., 400 μL/L designated as aCO2) and elevated CO2 (i.e., 800 μL/L designated as eCO2) by using light-CO2 climate chambers. Subsequently, the changes in several key nutrients and defensive compounds present in pea seedlings were assessed. Moreover, we assessed the growth, development, reproduction and changes in the nutritional components and enzyme activities of L. sticticalis as they fed on pea seedlings grown under aCO2 and eCO2. The results showed that the CO2 level significantly affected the measured indexes of pea seedlings and L. sticticalis. Host pea seedlings grown under eCO2 exhibited significant increases in soluble sugar (SS), soluble protein (SP) and total amino acid (TAA) contents by 42.52%, 77.06% and 62.50%, respectively, relative to those grown under aCO2. In addition, total phenol (TP), ethylene (ET) and jasmonic acid (JA) contents grown under eCO2 increased significantly by 20.60%, 71.72% and 36.22%, respectively, under eCO2 compared to aCO2. Furthermore, the duration of egg, larva and pupa of L. sticticalis was significantly shortened by 16.63%, 10.66% and 10.12%, respectively, while the adult longevity was significantly prolonged by 19.07% after feeding on pea seedlings grown under eCO2 in contrast to aCO2. Furthermore, for L. sticticalis, the content of SS, SP, TAA and free fatty acid was significantly increased, by 60.02%, 77.06%, 91.67% and 27.19%, respectively. Moreover, the enzyme activity of CAT, POD, CarE and GST was also enhanced by 56.70%, 63.89%, 128.08% and 93.45%, respectively, as they fed on pea seedlings grown under eCO2 in contrast to aCO2. The findings of our study revealed that eCO2 not only improved the nutritional quality but also altered the defensive compounds in the seedlings, which in turn affected the growth, development, reproduction and changes in the physiology of L. sticticalis.